Organocatalytic asymmetric synthesis of (-)-delta-coniceine based on sequential proline-catalyzed asymmetric alpha-amination-HWE olefination - Panchgalle, Sharad P.; Bidwai, Harshad B.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2010)
An efficient asymmetric synthesis of (-)-delta-coniceine via sequential proline-catalyzed asymmetric alpha-amination and Horner-Wadsworth-Emmons olefination of an aldehyde with excellent enantiomeric excess (>99%) and high yields (overall yield 44%) is described. (C) 2010 Elsevier Ltd. All rights reserved.